2005
DOI: 10.1227/01.neu.0000159887.03290.d1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Experimentally Induced Aneurysms with Stents

Abstract: This study demonstrates the possible shortcomings and problems of emerging stent techniques to treat intracerebral aneurysms, shows where technical advances have to be made, and describes in which cases of aneurysm morphology caution has to be exercised when considering an endovascular approach using stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…The incidence of in-stent stenosis is likely related to neointimal growth as has been previously suggested, 39 which can be secondary to endothelial injury. Endothelial cells play an integral role in the regulation of smooth muscle growth, and when that regulation is lost, neointimal proliferation can be seen that leads to stenosis.…”
Section: In-stent Stenosis and Perforator Patencymentioning
confidence: 74%
“…The incidence of in-stent stenosis is likely related to neointimal growth as has been previously suggested, 39 which can be secondary to endothelial injury. Endothelial cells play an integral role in the regulation of smooth muscle growth, and when that regulation is lost, neointimal proliferation can be seen that leads to stenosis.…”
Section: In-stent Stenosis and Perforator Patencymentioning
confidence: 74%
“…Of note, we did not include aneurysms treated with standard stent designs, as different groups have extensively evaluated such stents. 1,5,6,9,[11][12][13] For instance, measurements by Sadasivan et al 9 demonstrated a reduction in TDC peak of approximately 13%.…”
Section: Discussionmentioning
confidence: 99%
“…The current design is appropriate for lateral aneurysms, and work is in progress to extend the applicability to a larger variety of aneurysm geometries, such as bifurcation aneurysms. Further studies in more representative vessel morphologies, such as the rabbit elastase model, 5,25 are in progress, and initial results have been already presented. 26 It appears probable that the AVS may become a valued tool in the aneurysm treatment armamentarium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations